Anesthetic Management in Obese Patients Undergoing Laparoscopic Cholecystectomy: A Case Report - Pakardian, Insan Aqid; Dewi, Dewa Ayu Mas Shintya (Medicinus, 2025)
Background: Obesity is associated with various complications during general anesthesia, including apnea, hypoventilation, and challenges in intubation. In obese patients, these factors increase the anesthetic risks associated with laparoscopic cholecystectomy, a minimally invasive surgery performed to remove the gallbladder. This procedure is often indicated for gallstones causing inflammation, pain, or infection. Laparoscopic cholecystectomy involves small incisions, allowing most patients to recover quickly, return home the same day, and resume normal activities shortly thereafter. Compared to open cholecystectomy, the laparoscopic approach offers advantages such as faster recovery, reduced postoperative pain, and lower risk of complications. Methods: A 43-year-old female patient with a body weight of 120 kg, height of 155 cm, and a BMI of 49.9 kg/m² (classified as obesity) was initially scheduled for an open cholecystectomy. However, intraoperative evaluation by the surgeon led to a decision to switch to laparoscopic cholecystectomy. Anesthesia was induced using a propofol syringe pump, fentanyl (150 mcg), and atracurium (40 mg) as a muscle relaxant. Intubation was performed with video laryngoscopy, using an endotracheal tube (ETT) with a cuff size of 7. Result: During the operation, the patient's end-tidal CO2 (ETCO2) levels increased to 40 mmHg due to CO2 insufflation, leading to worsening respiratory acidosis. Complications such as these are common during laparoscopic procedures in obese patients and require timely management to prevent further deterioration. Conclusions: The patient’s condition was stabilized by employing specific intraoperative strategies, including positioning in reverse Trendelenburg, mild hyperventilation, and applying positive end-expiratory pressure (PEEP). These measures successfully reduced ETCO2 levels, demonstrating the importance of tailored anesthetic and ventilatory management in obese patients undergoing laparoscopic cholecystectomy.